Rechtsstaat als Aufgabe: ausgewählte Schriften und Vorträge; 1952 bis 1985 - Sarstedt, Werner (de Gruyter, 1987)
Werner Sarstedt: "Rechtsstaat als Aufgabe". Hrsg. von Gisela Sarstedt, Rainer Hamm, Wolfgang Köberer, Regina Michalke. Verlag Walter de Gruyter, Berlin/New York 1987. 351 S., geb., 168,- DM